MEMANFAATKAN WEBLOG UNTUK MELESTARIKAN BAHASA BALI PADA SISWA SEKOLAH DASAR DI DESA KINTAMANI KABUPATEN BANGLI - WIRASTUTI, N.M.A.E.D. (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014)
The target of this service program is to improve the capability and competence of teachers and students at SDN 2Kintamaniin applying information technology by providing them an introduction to computers and the internet, as well as providingtraining in how to create a free weblog using www.blogger.com , for globalcommunication. It also will be given counselingand knowledge about the use of computers for primary school students’ activities, the introduction of the Internet and the useof weblogs with Balinese language. Weblogcan be used for communicating about their activities at school and telltheirhobbies. Everything was told in Balinese language, where it is one way to preserve Balinese. Based on observations during theprogram, theparticipants was very excited and motivated, very interested and enthusiastic, so that the activity took placesmoothly. Participants can do the browsing and searching through the internet search facility that are www.google.com and www.yahoo.com . Participants can use the internet to search for information on educationalneeds and to know important siteson the internet. Participants understand how to use weblogs for free at www. blogger.com . Participants understand the partsof computer hardware. Keywords : weblog, teknologi informasi, computer, hardware, software